Male fertility: a summary overview of the publications April – September 2022 - D. S. Rogozin (Вестник урологии, 2023)
The article provides an overview of the most significant publications on male infertility. The main selection criteria were the practical relevance of the article, as well as the impact factor of the journal it was published, according to the SCImago Journal Rank (SJR). As a result, a list of 10 papers published in Q2-Q3 (April — September) 2022 was formed. The summary overview includes articles on the following topics: role of coronavirus infection in disorders of spermatogenesis, efficacy of hormonal stimulation before surgical sperm extraction, therapy consequences of diabetes mellitus on progeny reproductive health, new methods for selecting spermatozoa in ICSI, the efficacy of antioxidants, the safety of vaccines against SARS-CoV-2, the importance of genetic tests and predictive factors for micro-TESE success.